A new species of Neottia (Orchidaceae, Epidendroideae) from southwestern China - Jin, Xiaohua (Phytotaxa, 2014)
Neottia bicallosa, a new species from China, is described and illustrated. Neottia bicallosa is similar to Neottia karoana and N. microphylla, but differs from them by having oblong and erect lateral lobes with two fleshy calli between them, middle lobe elliptic and 3-lobed, and lateral lobules dentate.